Highly Efficient Polarizing Agents for MAS‐DNP of Proton‐Dense Molecular Solids. Issue 12 (1st February 2022) - Harrabi, Rania; Halbritter, Thomas; Aussenac, Fabien; Dakhlaoui, Ons; van Tol, Johan; Damodaran, Krishna K.; Lee, Daniel; Paul, Subhradip; Hediger, Sabine; Mentink‐Vigier, Frederic; Sigurdsson, Snorri Th.; De Paëpe, Gaël
Abstract: Efficiently hyperpolarizing proton‐dense molecular solids through dynamic nuclear polarization (DNP) solid‐state NMR is still an unmet challenge. Polarizing agents (PAs) developed so far do not perform well on proton‐rich systems, such as organic microcrystals and biomolecular assemblies. Herein we introduce a new PA, cAsymPol‐POK, and report outstanding hyperpolarization efficiency on 12.76 kDa U‐ 13 C, 15 N‐labeled LecA protein and pharmaceutical drugs at high magnetic fields (up to 18.8 T) and fast magic angle spinning (MAS) frequencies (up to 40 kHz). The performance of cAsymPol‐POK is rationalized by MAS‐DNP simulations combined with electron paramagnetic resonance (EPR), density functional theory (DFT) and molecular dynamics (MD). This work shows that this new biradical is compatible with challenging biomolecular applications and unlocks the rapid acquisition of 13 C– 13 C and 15 N– 13 C correlations of pharmaceutical drugs at natural isotopic abundance, which are key experiments for structure determination. Abstract : A new polarizing agent is introduced to efficiently polarize proton‐dense solids through dynamic nuclear polarization (DNP) ssNMR. This work shows that this new biradical can be used on organic microcrystals and biomolecular assemblies at high field and fast magic angle spinning (MAS). It notably unlocks the rapid acquisition of 13 C– 13 C and 15 N– 13 C correlations of pharmaceutical drugs at natural isotopic abundance, which are key experiments for structure determination.